Available nutrient status of a Typic Ustochrept as influenced by two irrigated and rainfed tropical agro-silvicultural plantations - BHADRARAY, SUBHENDU; RAO, Y S; AHMED, N (The Indian Journal of Agricultural Sciences, 2013)
An investigation was done during 1993-94 to study the effect of 10-year old irrigated and rainfed plantations of Eucalyptus tereticornis Smith and Leuceana leucocephala (Lam.) de Wit on available nutrient status of 2 related soil series belonging to Typic Ustochrept with the hypothesis that unless properly managed, those fast growing species may degrade the soil fertility in a long run, Raising either crops under rainfed condition depleted all the major nutrients and zinc over fallow both at the surface and down the profile. Among the plantations Eucalyptus preserved N and K better than Leuceana while the latter was superior with relation to P and secondary nutrients; micronutrients not showing any definite trend. Results could be explained in terms of nutrient demand, nutrient fixation in standing plantations and renewal through leaf fall and litter formation. Biomass and nutrient harvested/recycled data is expected to provide further insight to the problem. Pot culture experiment with upper 30 cm soil and ’HD 2428’ wheat (Triticum aestivum L. emend. Fiori & Paol.) as a test crop corroborated the field study. Soil under irrigated Eucalyptus gave wheat grain yield at par with treatment having recommended fertilizer dose in fallow while that under Leuceana was significantly lower. Available N, P, K and Zn were found to be important controlling factors towards wheat grain yield.